142k views
0 votes
Solve the system of equations. y = -6x + 9 y = -3x + 3 a. ( 3, -2) c. ( 2, -3) b. ( -2, -3) d. No solution

1 Answer

5 votes

For this case we have the following system of equations:


y = -6x + 9\\y = -3x + 3

Equating the equations we have:


-6x + 9 = -3x + 3

Adding 3x to both sides of the equation:


-6x + 3x + 9 = 3\\-3x + 9 = 3

Subtracting 9 from both sides of the equation:


-3x = 3-9\\-3x = -6

Dividing between -3 on both sides of the equation:


x = \frac {-6} {- 3}\\x = 2

We look for the value of "and":


y = -3 (2) +3\\y = -6 + 3\\y = -3

Thus, the solution of the system is (2, -3)

Answer:

(2, -3)

User Niladry Kar
by
6.0k points